EFFECT OF OPERATIONAL RISK ON THE PERFORMANCE OF LISTED INSURANCE COMPANIES IN NIGERIA - Olaiya, Kehinde Isiaq; Akingunola, Richard Ore-Oluwa; Alao, Abdul-Azeez Adeniyi (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: This study examines the determinants of profitability, measured by Adjusted Risk-Adjusted Return on Capital (Adjusted RAROC), in the context of listed insurance companies in Nigeria. Methods: Using a panel data regression analysis, we employ four models: pooled regression, fixed effects, random effects, and Difference Generalized Method of Moments (D-GMM), to explore the impact of operational risk factors, including the claims ratio, expense ratio, leverage, and firm size, on Adjusted RAROC. Results: The results indicate that leverage and firm size play significant roles in profitability, with higher leverage associated with increased profitability in some models. Conversely, the claims ratio shows a negative relationship with profitability, highlighting the importance of effective risk management. The expense ratio also exhibits a negative impact on profitability, emphasizing the need for efficient cost control. The D-GMM model, which addresses endogeneity issues, reveals that past performance and firm size are crucial predictors of future profitability. Conclusion and suggestion: Overall, the findings suggest that operational efficiency, risk management, and strategic financial decisions are essential for improving profitability in the Nigerian insurance sector.